Pouteria synsepala (Sapotaceae: Chrysophylloideae): a new species from the northern littoral of Bahia, Brazil - Popovkin, Alex V.; Faria, Aparecida D. De; Swenson, Ulf (Phytotaxa, 2016)
A new species of Pouteria from the Atlantic Forest area of the northern littoral of Bahia State, Brazil, is described and illustrated. Pouteria synsepala, whose epithet refers to the basally united sepals, a feature rare in the genus, resembles P. salicifolia in its narrowly elliptic leaves, but differs by the angle of secondary veins in relation to the midrib, pentamerous flowers, and stamens adnate to the corolla tube from the base to the tube orifice. Micromorphological studies revealed different patterns of stomate and wax morphology in the two species, providing further justification for the recognition of P. synsepala.